Results of a Survey of the National Psoriasis Foundation Medical Board on the Management of Ear Psoriasis. Issue 1 (January 2020) - Blake, Amy; Enos, Clinton; Armstrong, April W.; Garg, Amit; Gottlieb, Alice; Koo, John; Mehta, Nehal; Prussick, Ronald; Ryan, Caitriona; Schwartzman, Sergio; Siegel, Michael; Wu, Jashin J.; et al.
Background: There is limited literature on the occurrence and management of psoriasis involving the ear. Objective: To better understand psoriasis of the ear and current approaches for management. Methods: The Medical Board of the National Psoriasis Foundation was surveyed on the frequency and presentation of psoriasis of the ear, the types of examinations performed, and the rationale for choice of treatment. Results: In this survey, the observed frequency of ear psoriasis was wide (10%-70%). The scalp was the most common concurrent site of extra-auricular psoriasis. Inspection of the ear was commonly reported; however, 75% of respondents report not inspecting the canal. Topical corticosteroids were the most commonly used treatment. Systemic and biologic therapies are infrequently used. Limitations: This study is limited by the sample size of respondents. Not every question of the survey was answered by all those surveyed. Conclusions: Results from our survey suggest that the evaluation of psoriasis of the ear is often not complete. Inspection of the ear, including the canal, is recommended, especially if the scalp is involved. Routine inspection of the ear is recommended both to evaluate treatment response and for potential adverse side effects. In the setting of persistent ear disease, collaboration between dermatologists and otolaryngologists is encouraged.